Optimized Microencapsulation of Citrus aurantiifolia Peel Extract for Breast Cancer Therapy: In Silico-Supported Approach - Herjandi, Angelica Kurnia; Al-Anshori, Jamaludin; Julaeha, Euis (Trends in Sciences, 2025)
Breast cancer is the most prevalent cancer in Indonesia and is primarily treated by surgery or chemotherapy, often accompanied by adjuvant therapy. Citrus aurantiifolia peel extract exhibits potential as a natural anti-cancer compound. In silico screening identified 16 out of 95 candidate compound–protein interactions that demonstrated strong binding to key breast cancer-related targets (3ERT, 3PY0, 8I0M, 7PG6, and 1KV1), suggesting therapeutic relevance. Due to the extract’s environmental sensitivity, encapsulation is necessary to preserve its bioactivity. This study employed complex coacervation using a gelatin–gum arabic system crosslinked with glutaraldehyde, with formulation parameters optimized to improve encapsulation performance. The extract yield was 11.40%, and the optimal formulation ratios were 3.74:4 (extract/matrix), 0.066:4 (crosslinker/matrix), and 2:2 (gelatin/gum arabic). The resulting microcapsules achieved a yield of 54.21 ± 4.76%, an extract content of 3.67 ± 0.24%, and an encapsulation efficiency of 99.65 ± 0.09%, with spherical morphology and an average size of 1.249 ± 0.710 μm. Release studies followed Higuchi kinetics, indicating a controlled diffusion profile. These findings support the potential of C. aurantiifolia peel extract as a stable, encapsulated anti-cancer candidate for future therapeutic applications. HIGHLIGHTS Citrus aurantiifolia peel extract was explored for its potential as a natural anti-cancer agent. In silico screening identified 16 key compound–protein interactions related to breast cancer pathways. Encapsulation using gelatin–gum arabic via complex coacervation preserved extract bioactivity. Optimized microcapsules achieved 99.65 ± 0.09% encapsulation efficiency and Higuchi release kinetics. The study supports the extract’s potential as a stable, encapsulated candidate for breast cancer therapy. GRAPHICAL ABSTRACT